2008
DOI: 10.1007/s00114-008-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

Mate guarding and territorial aggression vary with breeding synchrony in golden whistlers (Pachycephala pectoralis)

Abstract: Male paternity assurance behaviour during the female fertile period has been widely documented amongst birds. In contrast, how sex-specific behavioural strategies vary with local breeding synchrony levels remains largely unknown. This is important because, in many species, intra-population patterns of extra-pair fertilisation rates, and hence cuckoldry risk, are known to vary with the number of simultaneously fertile females. Each sex may therefore differ in how they behave towards male conspecifics during dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Thus, when EPCs are mainly male initiated, as suggested by previous work in pied flycatchers (Björklund and Westman 1983;Alatalo et al 1987), a negative relationship between synchrony and EPP rates would occur when males prioritize avoiding cuckoldry over seeking paternity outside the pair bond (Birkhead and Biggins 1987;Westneat et al 1990). Accordingly, when the risk of cuckoldry is high, fairy martin males (Petrochelidon ariel) guard their mates more intensively, (Hammers et al 2009) whereas golden whistler males (Pachycephala pectoralis) are more aggressive towards intruders and remain closer to their mates (van Dongen 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when EPCs are mainly male initiated, as suggested by previous work in pied flycatchers (Björklund and Westman 1983;Alatalo et al 1987), a negative relationship between synchrony and EPP rates would occur when males prioritize avoiding cuckoldry over seeking paternity outside the pair bond (Birkhead and Biggins 1987;Westneat et al 1990). Accordingly, when the risk of cuckoldry is high, fairy martin males (Petrochelidon ariel) guard their mates more intensively, (Hammers et al 2009) whereas golden whistler males (Pachycephala pectoralis) are more aggressive towards intruders and remain closer to their mates (van Dongen 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Aggression between rival males is an important factor in gaining fertilizations because winning contests allows access to females (Bertram et al, 2011;Brown et al, 2007;Hurtado-Gonzales and Uy, 2010). More aggressive males will also guard mates to prevent sperm competition (Bateman and Toms, 1998;van Dongen, 2008;Watts, 1998). Hence reduced aggression towards rival males can lead to lowered reproductive success.…”
Section: Implications Of Altered Mating Behaviorsmentioning
confidence: 98%
“…We have insufficient information to comment on these assumptions but clearly a more detailed understanding of the EPC behaviour of both males and females would help to reveal the mechanism underlying this relationship between mate guarding and synchrony (Westneat & Stewart 2003). The observed increase in mate-guarding intensity with breeding synchrony is at odds with two previous studies that found males guarded less intensely when synchrony was high (Chuang-Dobbs et al 2001;van Dongen 2008). One possible explanation for this difference is that these other studies were on territorial species which would have regular interactions with far fewer conspecifics than the colonial fairy martins.…”
Section: Mate-guarding Intensity Breeding Synchrony and Extrapair Pamentioning
confidence: 71%
“…When synchrony is low, only a few females in the population will be concurrently fertile, and these individuals may attract more male-initiated EPC attempts than more synchronous females (Westneat et al 1990), promoting the necessity for mate guarding (Wagner et al 1996). Consequently, all else being equal, guarding may be expected to be most intense when the proportion of fertile females in the population is low (Wagner et al 1996;van Dongen 2008). Alternatively, males may invest more effort into seeking EPC when a higher proportion of females in the population are fertile (greater synchrony) and/or synchrony may facilitate the ability of females to compare and choose among extrapair males, promoting their propensity to engage in EPC (Stutchbury & Morton 1995).…”
mentioning
confidence: 99%